Kecemasan mahasiswa teknik komputer dan jaringan dalam menghadapi ujian praktik kejuruan - Lisa Putriani; Tyesa Sri Handayuni; Yola Eka Putri; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
The high level of student anxiety when facing exams causes negative effects that come from internal and external factors. Anxiety is an emotional state that is not soothing, such as feeling depressed in the face of adversity or before it occurs, which is characterized by feelings of worry, tension, and fear in certain situations. This study aims to describe the anxiety of vocational high school students in terms of cognitive, affective, and behavioral aspects. This research is quantitative research with descriptive methods. With a sample of 115 students using a proportional random sampling technique. The data were obtained by providing anxiety instruments in the face of vocational practice exams. Data were analyzed descriptively by determining the mean, standard deviation, and percentage. The results of the study reveal that the first, the level of anxiety of students majoring in Computer and Network Engineering in facing vocational practice exams is generally in the low category. Second, the level of anxiety of students majoring in Computer and Network Engineering in facing vocational practice exams seen from the cognitive aspect is generally in the medium category. Third, the level of anxiety of students majoring in Computer and Network Engineering in facing vocational practice exams seen from the affective aspect is generally in the medium category. Fourth, the level of anxiety of students majoring in Computer and Network Engineering in facing vocational practice exams seen from the aspect of behavior is generally in the medium category.